Economics of Underutilized Crop Production in Mizoram - Lalrinsangpuii, Lalrinsangpuii; Malhotra, R.; Priscilla, Laishram (Indian Journal of Hill Farming, 2016)
The study was carried out on 120 farmers in Mizoram during the year 2014-15 to analyse the cost and returns, resource use efficiency and constraints faced by the farmers in the cultivation of underutilized crops. The farms were classified into small, medium and large categories using cumulative square root frequency method of stratification. The total cost of cultivation was estimated to be rupees 24010/ha for overall farm. Among the different categories of farms the total cost of cultivation was highest on medium farms followed by large farms and small farms, respectively. The overall farms had realized gross income of rupees 31657 from the underutilized crops. Among the various categories of farms, the gross income was highest on large farms rupees  32850 followed by medium (rupees 32081) and small farms (rupees 30039). The Cobb-Douglas production function indicated that response to land holding and human labour was found to be positive and significant. High cost of inputs was the most serious problem stated by the farmers in crop production followed by unavailability of financial support.